2020
DOI: 10.1128/aem.00579-20
|View full text |Cite
|
Sign up to set email alerts
|

In-Depth Longitudinal Study of Listeria monocytogenes ST9 Isolates from the Meat Processing Industry: Resolving Diversity and Transmission Patterns Using Whole-Genome Sequencing

Abstract: ABSTRACT Listeria monocytogenes is a pathogen mostly associated with the consumption of ready-to-eat foods and can cause severe disease and death. It can be introduced into food chains from raw materials, but often the contamination source is the food production environment, where certain clones can persist for years. In the meat chain, ST9 is one of the most commonly encountered Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 71 publications
3
63
0
Order By: Relevance
“…It has been previously shown that the cgMLST analysis is a very useful molecular tool to assess the L. monocytogenes structure population [ 5 , 6 , 27 , 30 , 34 , 35 , 36 ]. In the present study, genetically closely related strains of the SL2-ST145-CT375 type were isolated in nine administrative provinces (voivodeships) of Poland during 2015-2018, mostly from raw meat ( Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been previously shown that the cgMLST analysis is a very useful molecular tool to assess the L. monocytogenes structure population [ 5 , 6 , 27 , 30 , 34 , 35 , 36 ]. In the present study, genetically closely related strains of the SL2-ST145-CT375 type were isolated in nine administrative provinces (voivodeships) of Poland during 2015-2018, mostly from raw meat ( Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, genetically closely related strains of the SL2-ST145-CT375 type were isolated in nine administrative provinces (voivodeships) of Poland during 2015-2018, mostly from raw meat ( Table S1 ). This fact can be explained by, e.g., the ability of such isolates to persist in food production environments or introduction of the bacteria from outside sources, e.g., from the meat supplying slaughterhouses [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the possible evolution over time of a population of persistent strains in its environment, a relaxed 25-SNPs threshold was applied to define strains as belonging to the same cluster [ 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Also, CC8 clones were associated with human listeriosis cases and outbreaks across Canada for more than two decades [26]. Several studies reported the favorable settlement and the persistence of CC9 in meat processing environments and equipment for several years [6,24,[27][28][29][30]. This clone possesses higher stress resistance and benzalkonium chloride tolerance genes and a biofilm formation ability that contributes to its persistence [29,30].…”
Section: Low Genetic Heterogeneity and The Widespread Prevalence Of Mmentioning
confidence: 99%